2014
DOI: 10.1007/978-3-642-45106-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Intracellular Dynamics of Neurotrophin and Its Receptors. Implications for Neurotrophin Signaling and Neuronal Function

Abstract: Neurons possess a polarized morphology specialized to contribute to neuronal networks, and this morphology imposes an important challenge for neuronal signaling and communication. The physiology of the network is regulated by neurotrophic factors that are secreted in an activity-dependent manner modulating neuronal connectivity. Neurotrophins are a well-known family of neurotrophic factors that, together with their cognate receptors, the Trks and the p75 neurotrophin receptor, regulate neuronal plasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 191 publications
2
39
0
Order By: Relevance
“…These endosomes are likely different from the TrkA‐positive endosomes because p75 has different kinetics of internalization compared with TrkA [Bronfman et al, ; McCaffrey et al, ]. In contrast to what has been observed for the Trks, p75 is poorly targeted to the degradative pathway (i.e., late endosomes and lysosomes) [Bronfman et al, ]. We have shown that after internalization in PC12 cells and sympathetic neurons, p75 accumulates in the recycling endosomes and multivesicular bodies (MVB) and is ready for exosomal release, which is a ligand‐dependent process; therefore, increased internalization augmented the p75 content in exosomes after neuronal depolarization [Escudero et al, ].…”
Section: Membrane Dynamics and The Regulation Of Bdnf Signaling And Nmentioning
confidence: 86%
See 2 more Smart Citations
“…These endosomes are likely different from the TrkA‐positive endosomes because p75 has different kinetics of internalization compared with TrkA [Bronfman et al, ; McCaffrey et al, ]. In contrast to what has been observed for the Trks, p75 is poorly targeted to the degradative pathway (i.e., late endosomes and lysosomes) [Bronfman et al, ]. We have shown that after internalization in PC12 cells and sympathetic neurons, p75 accumulates in the recycling endosomes and multivesicular bodies (MVB) and is ready for exosomal release, which is a ligand‐dependent process; therefore, increased internalization augmented the p75 content in exosomes after neuronal depolarization [Escudero et al, ].…”
Section: Membrane Dynamics and The Regulation Of Bdnf Signaling And Nmentioning
confidence: 86%
“…It was later shown that neurotrophins have multiple functions in the CNS including regulation of neuronal morphology and plasticity. Over the last few years, it has been shown that neurotrophins can be secreted from different types of cells including neurons to stimulate paracrine and autocrine actions [Bronfman et al, , and references therein].…”
Section: Neurotrophin Receptors and Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it will be interesting to find out whether signaling endosomes might also play a role in synapse to nucleus signaling, analogous to their well-established role in survival and maintenance signaling in the axonal compartment [98,99]. A recent study used microfluidics chambers to investigate dendrite to nucleus signaling in embryonic cortical neurons, demonstrating that dendritic application of BDNF elicited a transcriptional response in the soma [100].…”
Section: Reviewmentioning
confidence: 95%
“…During the initiation and progression of pancreatic cancer, ERBB signaling pathway has been confirmed to participate in the biological processes, validating our newly presented algorithm [83]. Neurotrophins have firstly been identified as a group of proteins that contribute to the survival, development, and function of neurons [84]. However, recent publications have revealed that neurotrophins may participate in the survival and proliferation of various cell types including the tumor cells [8587].…”
Section: Resultsmentioning
confidence: 53%